'No easy fix': The Supervised Injection Site Debate in Canada - Zhang, Kelly (Université d'Ottawa / University of Ottawa, 2014)
Supervised injection sites (SISs) have become subject to much political and social controversy in Canada since the late 1990s. Since the implementation of North America’s first SIS, Insite, in 2003 in Vancouver, the controversy has reached new levels. Despite the increasing evidence base available regarding the effectiveness of SISs as a harm reduction strategy trans-nationally, the implementation of this intervention in Canada prevails within public and parliamentary debates. Guided by the theoretical contributions of Joel Best (2008) on claims-making and the construction of social problems, this thesis explores the SIS debate in Canada and the assertions advanced with respect to the implementation of SISs. Building on the available literature, the author identifies numerous types of claims advanced by proponents and opponents of SISs through a qualitative content analysis of 164 newspaper documents from The Vancouver Sun, The Ottawa Sun and The Ottawa Citizen. It was determined that claimsmakers often present the intervention as a solution to the ‘drug problem’ or part in parcel of the problem. Opponents in particular attempt to construct the intervention as harmful for the community in that the implementation of a SIS would exacerbate various aspects of the ‘drug problem’ including drug abuse and crime. Very rarely, however, claimsmakers suggest the SIS is merely one strategy to addressing public health issues related to injection drug use and that there is ‘no easy fix’ to this ‘drug problem’. Further, the author applies the findings from this analysis to make sense of the Canadian federal government’s proposed policy response, The Respect for Communities Act, towards the establishment of SISs.
Keywords: Supervised injection site; Illicit drugs; Insite; Politicization; Claims-making; Drug policy